KARAKTERISTIK EMULSI SANTAN DAN MINYAK KEDELAI YANG DITAMBAH GUM ARAB DAN SUKROSA ESTER [Emulsion Characteristics of Coconut Milk and Soybean Oil Added by Gum Arabic, Sucrose Ester] - Laksmi Hartayanie; Melisa Adriani; - Lindayani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
High saturated fatty acid content in coconut milk can be reduced by adding unsaturated fat. Pretreatment like pasteurisation, homogenization or stabilizer and emulsifier addition are essential to prevent emulsion deterioration that could happen in few hours. This study aimed to determine the most appropriate combination of gum arabic and sucrose ester induced the good emulsion stability based on physical and chemical characteristics. Furthermore this study also aimed to determine correlation between creaming index and other characteristics of coconut milk emulsion. Emulsion stability of mixed coconut milk in sterile glass bottles was observed for 7 days under 23-24°C Stabilizer and emulsifier added were gum arabic and sucrose ester in five combinations such as 6% gum arabic, 0.3% sucrose ester, 6% gum arabic + 0.3% sucrose ester, 3% gum arabic + 0.15% sucrose ester and 4.5% gum arabic + 0.225% sucrose ester then the physical and chemical characteristic changes were evaluated. Physical characteristic observed were creaming index, total colour change, viscosity and droplet distribution, meanwhile chemical characteristics observed were pH, TBA value, and protein content. Data were analyzed by One Way Anova at 95% significant level to determine differences among treatments. Bivariate Pearson Correlation was used in order to determine the intraction among sample characteristics. The data showed that, gum arabic and sucrose ester can keep the emulsion stability. The combination of 4.5% gum arabic and 0.225% sucrose ester provide the best physicochemical characteristics, which were the lowest creaming index and decreasing viscosity, and uniform droplet distribution.